The river eaudiobook A novel. - Heller, Peter (Random House Audio, 2019)
A Nominee for the 2020 Edgar Allan Poe Awards NATIONAL BESTSELLER "A fiery tour de force… I could not put this book down. It truly was terrifying and unutterably beautiful." –Alison Borden, The Denver Post From the best-selling author of The Dog Stars, the story of two college students on a wilderness canoe trip—a gripping tale of a friendship tested by fire, white water, and violence Wynn and Jack have been best friends since freshman orientation, bonded by their shared love of mountains, books, and fishing. Wynn is a gentle giant, a Vermont kid never happier than when his feet are in the water. Jack is more rugged, raised on a ranch in Colorado where sleeping under the stars and cooking on a fire came as naturally to him as breathing. When they decide to canoe the Maskwa River in northern Canada, they anticipate long days of leisurely paddling and picking blueberries, and nights of stargazing and reading paperback Westerns. But a wildfire making its way across the forest adds unexpected urgency to the journey. When they hear a man and woman arguing on the fog-shrouded riverbank and decide to warn them about the fire, their search for the pair turns up nothing and no one. But: The next day a man appears on the river, paddling alone. Is this the man they heard? And, if he is, where is the woman? From this charged beginning, master storyteller Peter Heller unspools a headlong, heart-pounding story of desperate wilderness survival.